Framework for the assessment of interaction between CO2 geological storage and other sedimentary basin resources - Michael, K.; Whittaker, S.; Varma, S.; Bekele, E.; Langhi, L.; Hodgkinson, J.; Harris, Brett (Royal Society of Chemistry, 2016)
Sedimentary basins around the world considered suitable for carbon storage usually contain other natural resources such as petroleum, coal, geothermal energy and groundwater. Storing carbon dioxide in geological formations in the basins adds to the competition for access to the subsurface and the use of pore space where other resource-based industries also operate. Managing potential impacts that industrial-scale injection of carbon dioxide may have on other resource development must be focused to prevent potential conflicts and enhance synergies where possible. Such a sustainable coexistence of various resource developments can be accomplished by implementing a Framework for Basin Resource Management strategy (FBRM). The FBRM strategy utilizes the concept of an Area of Review (AOR) for guiding development and regulation of CO2 geological storage projects and for assessing their potential impact on other resources. The AOR is determined by the expected physical distribution of the CO2 plume in the subsurface and the modelled extent of reservoir pressure increase resulting from the injection of the CO2. This information is used to define the region to be characterised and monitored for a CO2 injection project. The geological characterisation and risk- and performance-based monitoring will be most comprehensive within the region of the reservoir containing the carbon dioxide plume and should consider geological features and wells continuously above the plume through to its surface projection; this region defines where increases in reservoir pressure will be greatest and where potential for unplanned migration of carbon dioxide is highest. Beyond the expanse of the carbon dioxide plume, geological characterisation and monitoring should focus only on identified features that could be a potential migration conduit for either formation water or carbon dioxide.